2020
DOI: 10.1016/j.jmgm.2020.107690
|View full text |Cite
|
Sign up to set email alerts
|

Polyacylated anthocyanins constructively network with catalytic dyad residues of 3CLpro of 2019-nCoV than monomeric anthocyanins: A structural-relationship activity study with 10 anthocyanins using in-silico approaches

Abstract: Coronavirus epidemic 2019 (COVID-19), caused by novel coronavirus (2019-nCoV), is newly increasing worldwide and elevating global health concerns. Similar to SARS-CoV and MERS-CoV, the viral key 3-chymotrypsin-like cysteine protease enzyme (3CL Pro ), which controls 2019-nCoV duplications and manages its life cycle, could be pointed as a drug discovery target. Herein, we theoretically studied the binding ability of 10 structurally different anthocyanins with the catalytic dyad residues o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 34 publications
0
26
0
3
Order By: Relevance
“…These studies have shown that people with a specific diet, especially polyphenols-rich ones, are at reduced risk for a variety of diseases ( Rasouli et al , 2017 ; Yahfoufi et al , 2018 ). Additionally, polyphenols are developing therapeutic tools for controlling and protecting the body from several autoimmune disorders due to their immunomodulatory effects ( Khalifa et al , 2020 ; Khan et al , 2019 ). The immune modulation effect of polyphenols is related to the impact on immune cells, pro-inflammatory gene expression, and modulate cytokines production ( Yahfoufi et al , 2018 ).…”
Section: The Potential Uses Of Plant Extracts Containing Polyphenolsmentioning
confidence: 99%
See 4 more Smart Citations
“…These studies have shown that people with a specific diet, especially polyphenols-rich ones, are at reduced risk for a variety of diseases ( Rasouli et al , 2017 ; Yahfoufi et al , 2018 ). Additionally, polyphenols are developing therapeutic tools for controlling and protecting the body from several autoimmune disorders due to their immunomodulatory effects ( Khalifa et al , 2020 ; Khan et al , 2019 ). The immune modulation effect of polyphenols is related to the impact on immune cells, pro-inflammatory gene expression, and modulate cytokines production ( Yahfoufi et al , 2018 ).…”
Section: The Potential Uses Of Plant Extracts Containing Polyphenolsmentioning
confidence: 99%
“…These studies unleashed that anthocyanins and/or tannins with specific structure could be used as effective anti-COVID-19 natural components. Meanwhile, Fig 1 B. portrayed the interaction between tannins with SARS-CoV-2-3CLpro ( Khalifa, Nawaz, et al , 2020 ; Khalifa, Zhu, et al , 2020 ). We summarized the antiviral activities from the recent studies of natural polyphenols from several plants and their mode of action against CoVs ( Table 4 ).…”
Section: The Potential Uses Of Plant Extracts Containing Polyphenolsmentioning
confidence: 99%
See 3 more Smart Citations